Arithmetic Average Transformation Technique to Solve Multi-Objective Quadratic Programming Problem - Sulaiman, Najmaddin A.; Abulrahim, Basiya K. (Sulaimani Journal for Pure and Applied Sciences, 2013)
In this paper, we used arithmetic average transform technique for solving the multi-objective quadratic programming problem (MOQPP) to single-objective quadratic programming problem(SOQPP), through a new method using arithmetic average, then solve the problems by Wolfe's method [3,12].The obtain results are compared with that of modified method given in [11] and with the Chandra Sen. method [7].
Keywords: MOQPP; arithmetic average